2007
DOI: 10.1007/s00421-007-0539-z
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary drinking and hydration in non-acclimatized girls exercising in the heat

Abstract: The intent of this study was to assess the influence of drink flavor and composition on voluntary drinking and hydration status in girls exercising intermittently in the heat (35 +/- 1 degrees C, 45-50% relative humidity). Twelve physically active, nonacclimatized girls (9-12 years) performed three 3 h identical sessions, each consisting of four 20 min cycling bouts at 50% (VO(2max)), separated by 25 min of rest. One of the three beverages (chilled to 8-10 degrees C) was assigned to each session: unflavored wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
2
16
2
3
Order By: Relevance
“…We conWrmed this Wnding by showing that a Xavored beverage containing carbohydrate and NaCl increased voluntary drink intake by 32% (compared to unXavored water) in trained, heat-acclimatized boys who experienced much higher sweating rates during prolonged exercise (Rivera-Brown et al 1999). In contrast, a recent study by Wilk et al (2007) showed that beverage Xavoring, but not the addition of NaCl, enhanced voluntary drinking in non-acclimatized girls exercising in the heat and that even thirst-guided drinking of plain water was suYcient to maintain euhydration in these girls.…”
Section: Introductionmentioning
confidence: 78%
“…We conWrmed this Wnding by showing that a Xavored beverage containing carbohydrate and NaCl increased voluntary drink intake by 32% (compared to unXavored water) in trained, heat-acclimatized boys who experienced much higher sweating rates during prolonged exercise (Rivera-Brown et al 1999). In contrast, a recent study by Wilk et al (2007) showed that beverage Xavoring, but not the addition of NaCl, enhanced voluntary drinking in non-acclimatized girls exercising in the heat and that even thirst-guided drinking of plain water was suYcient to maintain euhydration in these girls.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, in non-acclimatised girls exercising in the heat, voluntary drinking was enhanced with flavoured compared with unflavoured water regardless of combination with CHO and NaCl, but hydration was promoted to a greater extent with the drink containing CHO and NaCl (Wilk et al 2007). Similarly, there was a tendency towards a lower hypohydration and greater fluid retention with the consumption of a CHO plus NaCl drink in trained, heat-acclimatised girls with high sweating rates, although voluntary dehydration was not prevented completely (Rivera-Brown et al 2008).…”
Section: Sports Drinks and Hydrationmentioning
confidence: 94%
“…Consequently, succeeding investigations tended to utilize experimental designs in which the child was fully hydrated at the start of an exercise session and was allowed to drink at least ad libitum during the session; the degree of dehydration reached in these studies seldom exceeded 1% of initial body weight (Meyer et al, 1995;Rivera-Brown et al, 1999;Rivera-Brown et al, 2008;Wilk et al, 2000;Wilk & Bar-Or, 1996;Wilk et al, 2007). It remains unclear, however, to what extent these artificial conditions truly reflect the young athlete's real-life responses, when competing under hot climatic conditions.…”
Section: Federation Of State High School Associations 2009) In Canamentioning
confidence: 99%